Pengembangan Label Pintar untuk Indikator Kesegaran Daging Sapi pada Kemasan - Arjun Nurfawaidi; Bambang Kuswandi; Lestyo Wulandari (Pustaka Kesehatan, 2018)
Meat is a high nutritional food that rich of protein, fat, and sugar. Smart label has been applied as a beef freshness detector. Two types of pH indicator have been used i.e bromocresol purple (BCP) and methyl red (MR) as dual indicator freshness. The objective of this research was to determine the beef freshness using smart label at room temperature. The color change of the smart label was examined by imageJ software to determine the freshness degree using the mean RGB value. The beef was examined every 2 hours for pH and total volatile base (TVB-N) analysis during the 24 hours storage at room temperature. The result showed that color indicator will change according to the beef freshness, bromocresol purple turned from yellow to purple (mean RGB 171.465 ± 1.122) and methyl red turned from red to yellow (mean RGB 162.082 ± 1.315). The beef freshness at room temperature decreased as the pH increase from 5.61 to 6.23 along with the color change of smart label. Furthermore, the color would change when 0.022 %N of TVB-N has been reached. Therefore, the beef freshness can be determined by using smart label based on dual indicator of bromocresol purple and methyl red in room temperature. Keywords: beef freshness, smart label, pH, TVB